Family Financial Management through Islamic Family Wealth Management - Fadilla Fadilla; Ahmad Farhan; Choiriyah Choiriyah (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
During the global financial industry 5.0, it was easier for people to make loans both to banks or make loans online. To meet the needs of their lives, the community also no longer needs to come to the market, it is enough to press one of the applications on their respective mobile phones. The convenience of this technology gives birth to a culture of consumerism in society and people are more easily in debt. The research method used in this research is library research. This study seeks to explain to the community how important it is to control finance with the Islamic Family wealth management approach. The results suggest to families to fulfil the main points first in the order of (1) Wealth Accumulation, (2) Wealth protection, (3) Wealth purification, (4) Wealth Distribution.